Vaping: Realities in its Effect on Oral Health - Sudipta Sahu1 , Ramesh Nagarajappa2 , Kajal Kiran Sahoo3 , Debashruti Naik4 , Nikita Sahu1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Twentieth-century shows a great increase in the popularity of E-cig or electronic cigar or Electronic NicotineDelivering System (ENDS).When smoking is considered as a leading cause of preventable death and strictmeasures had been taken to limit smoking in public places, this ENDS is gaining popularity worldwideamong the youngsters. A new term Vaping is given to the process of consuming nicotine or other substancethrough a vaporising tool or popularly called E-cigar. People are using it as a smoking cessation tool also,though this fact is being debatable after many types of research on it. The increasing use of it, along with alack of knowledge of its health effect both short and long term is worrying.